(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the problem of axiology, the history of its development and the results of research. The content of axiology is based on the need and circumstances of its development in students. The article also provides suggestions and recommendations for the development of a corporate system, stages and pedagogical model of development in the history of philosophical development of value problems.